Effects of brown and green seaweeds on nutrient digestibility, growth performance, carcass characteristics and health performance in broiler chickens - Naeem, Azizi Mohammad (2021)
It has widely reported that seaweed has bioactive molecules that have been examined for health-promoting effects on livestock. Whereas there is still a lack of research to describe the effects of seaweed on broiler apparent ileal digestibility of nutrients, production and health performances. Two experiments were conducted to study the effects of brown seaweed and green seaweed on broiler chickens’ nutrient digestibility, growth performance, carcass characteristics, small intestine histomorphology, blood plasma profiles, antioxidant and immune statuses. In the first experiment of this study, the nutritional properties of brown and green seaweed were analysed. A digestibility trial was conducted to investigate the effect of seaweeds on crude protein, crude fibre, ether extract, dry matter, organic matter, amino acids and minerals apparent ileal digestibility. A total of 36 broiler chickens (Cobb 500) were randomly distributed into two dietary treatments containing 90.30% of each seaweed type. The data analysis for both experiments was conducted using the General Linear Model of the Statistical Analysis System by one-way ANOVA. Duncan's Multiple Range Test was used to compare the significant difference between the treatments at p < 0.05. The results showed that brown seaweed and green seaweed had 59.8 and 55.88% crude protein, 1.28 and 0.30% ether extract, 5.78 and 5.19% crude fibre, 29.19 and 34.68% carbohydrates, and 9.7 and 9.14% ash contents, respectively. Brown seaweed and green seaweed contained a high amount of micromineral K (2.96 and 2.20%) and trace elements Fe (14.67 and 11.73 mg. 100 g−1). The gross energy value of brown seaweed and green seaweed was 6171.53 and 6150.26 kcal/kg, respectively. The digestibility results showed that the apparent ileal digestibility of brown seaweed and green seaweed was 88.82 and 86.8% for ether extract, 82.03 and 80.6% for organic mater, 60.69 and 57.80% for crude protein, 48.56 and 44.02% for crude fibre, and 17.97 and 19.40% for ash contents, respectively. The apparent ileal digestibility of various amino acids was 40.96 to 77.54%. The results of Ca, Na, K, Mg, Zn, Cu, Fe and Mn digestibility that among the selected minerals, Ca had the highest level (96.91, 97.61%) apparent ileal digestibility. Furthermore, both seaweed types exhibited a remarkable antioxidant activity. In the second experiment, a feeding trial was conducted to determine the effects of brown and green seaweed on growth performance, carcass characteristics and health performance in broiler chickens. A total of 504 one-day-old male broiler chicks (Cobb 500) were randomly distributed into twelve dietary treatments, containing: Basal diet (T1), basal diet + vitamin E (100 mg/kg feed) (T2), and basal diet + 0.25, 0.50, 0.75, 1 and 1.25% brown seaweed and green seaweed inclusions (T3-T12). The result demonstrated that different brown seaweed and green seaweed inclusion levels increased (p < 0.05) the growth performance of broiler chickens during the starter period. Different brown and green seaweed levels increased (p < 0.05) the crude protein digestibility during the starter period. The birds fed 0.25 and 0.50% brown seaweed, and 0.25, 0.75 and 1% green seaweed had increased (p < 0.05) breast meat crude protein content. In week three, birds fed 0.50, 0.75, and 1.25% brown seaweed had significantly higher jejunum villi height. Regarding the plasm lipid profile, the total cholesterol and highdensity lipoprotein levels were higher (p < 0.05) for birds fed 0.75 and 1% brown seaweed compared to the negative and positive control groups. Different levels of green seaweed (0.75, 1 and 1.25%) significantly improved plasma immunoglobulin A and immunoglobulin G concentrations. Birds fed 0.50% brown seaweed, and 0.25% and 0.50% of green seaweed increased (p < 0.05) the caecal Lactobacillus population. Meanwhile, the 0.75% inclusion level of brown seaweed and green seaweed decreased (p < 0.05) the Escherichia coli population compared to the negative control group. Brown and green seaweed also increased propionic acid and total volatile fatty acids in the caecal digesta. Various brown and green seaweed inclusion levels significantly upregulated the interleukin-6, interleukin-10 and interferon gamma gene mRNA expression. The result showed that the mRNA expression of the growth hormone receptor gene was higher (p < 0.05) for birds fed 0.50% and 0.75% of green seaweed. Furthermore, birds feed 0.50% brown seaweed and 0.25%, 0.50% and 0.75% of green seaweed significantly upregulated the hepatic insulin-like growth factor-1 mRNA expression. The hepatic superoxide dismutase-1 mRNA expression was higher for birds fed 0.50% and 0.75% of brown seaweed. In conclusion, the crude protein content was the major component of dried brown and green seaweed. Regarding the digestibility of 90.30% seaweed-based diets, the results showed that broiler chickens utilised brown and green seaweed with higher apparent ileal digestibility of organic matter, ether extract and minerals, moderate crude protein and amino acids, and low apparent ileal digestibility of crude fibre and ash contents. The results suggested that adding green and brown seaweed up to 1.25% in broiler chicken diet can improve bird growth performance and nutrient digestibility during the starter period. Brown and green seaweed also improved bird’s meat crude protein content. Different brown seaweed and green seaweed levels showed immunostimulating effects due to enhancing immunoglobulins concentrations, regulating the balance of intestinal microbiota, and increasing inflammatory mediators without adverse effects on meat quality, carcass characteristics, and plasma lipid profile. Discoveries from the current research are helpful for further studies investigating the mechanisms and components underlying the growth and digestibility enhancing effects during the starter period of birds.